(untitled) (Journal Of Educational and Psychological Researches, 2014)
The old ways of education has not been able to achieve the ultimate goal in the development of the child’s personality and prepared for public life , so shall educators to adopt modern methods of learning such as cooperative learning , which takes into account the considerations psychology of children and their level of mental , as the collective learning is important for children mighty and vulnerable children and so by placing the child in front of something significant tangible and choose topics of relevance to the concerns of the child himself . ( Maroni , 2008 : 101-102 ) . Consisted importance of research of the most important goals of community child care and upbringing proper education to create him a good citizen intact, and this is what he referred to ) Comenius 1592-1670 ) that the child the gift of God’s gifts and that people should appreciate this divine gifts . He was always seen to nature and its as good of a role model in raising children , the semi- Ch ild Seed Plant , also likened the bird small , semi childhood disconnect from a spring seasons of the year . ( Orontes , 1986 : 98-99 ) . , And current research aims to: build a training program for cooperative learning for children Riyadh age (5-6 years) . Determined search all public kindergartens affiliated to the Directorate of Education in Baghdad Karkh first . Most important findings of her research : The kindergarten children acquired good skills as well as many aspects of thinking .. learning program Altaawi reduced the concentration of the child about the same . Cooperative learning program helped the kids on exploration , tolerance and self-confidence , and contributed to make the child a social . The research has included some of the recommendations and proposals task